2023
DOI: 10.1101/2023.11.01.565123
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The small molecule CBR-5884 inhibits theCandida albicansphosphatidylserine synthase

Yue Zhou,
Gregory A. Phelps,
Mikayla M. Mangrum
et al.

Abstract: Systemic infections byCandida spp.are associated with high mortality rates, partly due to limitations in current antifungals, highlighting the need for novel drugs and drug targets. The fungal phosphatidylserine synthase, Cho1, fromCandida albicansis a logical antifungal drug target due to its importance in virulence, absence in the host and conservation among fungal pathogens. Inhibitors of Cho1 could serve as lead compounds for drug development, so we developed a target-based screen for inhibitors of purifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…The other screen identified bleomycin, but it was also found that this compound affects phospholipid-associated processes rather than targeting C. albicans PS synthase directly [ 245 ]. Recently, Zhou et al identified a molecule, CBR-5884 ( Table 3 ), that inhibits both purified PS synthase and its function in vivo, with a K i of 1550 ± 245.6 nM [ 121 ]. This molecule acts as a competitive inhibitor for serine, thus having the potential for further development.…”
Section: Cell Membrane Biosynthesis Enzymesmentioning
confidence: 99%
“…The other screen identified bleomycin, but it was also found that this compound affects phospholipid-associated processes rather than targeting C. albicans PS synthase directly [ 245 ]. Recently, Zhou et al identified a molecule, CBR-5884 ( Table 3 ), that inhibits both purified PS synthase and its function in vivo, with a K i of 1550 ± 245.6 nM [ 121 ]. This molecule acts as a competitive inhibitor for serine, thus having the potential for further development.…”
Section: Cell Membrane Biosynthesis Enzymesmentioning
confidence: 99%